The definitive guide to project management : the fast track to getting the job done on time and on budget. - Nokes, Sebastian, ....-; Kelly, Sean, 1960- (Harlow : Prentice Hall, 2007)
Successful project management is delivering your projects on time, to brief and within budget. "The Definitive Guide to Project Management" shows you step by step how to master the techniques of effective project management so that your projects deliver what you want, every time. Suitable for both beginners and more experienced project managers, "The Definitive Guide to Project Management" is the essential companion for anyone looking to develop their project management skills. Revised and improved to follow the presigious PMI certification scheme, its indispensable advice can be put to work immediately. Inside you will find key exam questions, templates and action checklists to help you at each stage of your well-executed project. Get the job done and on time with "The Definitive Guide to Project Management" The Definitive Business Series will ensure you get up to speed fast with all the business essentials you need to be a success.With their guided step-by-step approach the latest practical business techniques and concepts and their easy-to-read style, The Definitive Business Series cover every aspect of the topic from the business basics to the essential skills needed to progress in your career.